2021
DOI: 10.1039/d1dt00121c
|View full text |Cite
|
Sign up to set email alerts
|

Quasilinear 3d-metal(i) complexes [KM(N(Dipp)SiR3)2] (M = Cr–Co) – structural diversity, solution state behaviour and reactivity

Abstract: The synthesis of quasilinear metal(i) silylamides [KM(N(Dipp)SiR3)2] of chromium to cobalt, their diverse speciation in solid state and solution as well as their reactivity towards alkynes are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 54 publications
2
43
0
1
Order By: Relevance
“…Similarly, salt‐like compounds, such as KN(SiMe 3 ) 2 or KCH 2 Ph, form interesting at‐complexes (e. g. [KM(CH 2 Ph){N(SiMe 3 ) 2 } 2 ] or [KFe{N(SiMe 3 ) 2 } 3 ]), which evoke distinct reactivities [18,19] . In addition to hexamethyldisilazanides, metal(II) complexes with bulkier silyamide ligands (e. g. −N(SiMe 2 Ph) or −N(Dipp)SiR 3 ) (Dipp=2,6‐di‐ iso ‐propylphenyl) also found their use with a persistent quasilinear geometry [20–25] . In recent reports it was also shown that such divalent 3d‐metal silylamides can be reduced giving linear, monovalent complex anions [22,25–29] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, salt‐like compounds, such as KN(SiMe 3 ) 2 or KCH 2 Ph, form interesting at‐complexes (e. g. [KM(CH 2 Ph){N(SiMe 3 ) 2 } 2 ] or [KFe{N(SiMe 3 ) 2 } 3 ]), which evoke distinct reactivities [18,19] . In addition to hexamethyldisilazanides, metal(II) complexes with bulkier silyamide ligands (e. g. −N(SiMe 2 Ph) or −N(Dipp)SiR 3 ) (Dipp=2,6‐di‐ iso ‐propylphenyl) also found their use with a persistent quasilinear geometry [20–25] . In recent reports it was also shown that such divalent 3d‐metal silylamides can be reduced giving linear, monovalent complex anions [22,25–29] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent reports it was also shown that such divalent 3d‐metal silylamides can be reduced giving linear, monovalent complex anions [22,25–29] . These were employed in bond activation and substrate reduction [19,24,27,29–34] . Here, the unique role of the low‐coordinate environment of the low‐valent metal as well as the weak field of silylamide ligands became evident, causing unusual higher‐spin imido cobalt complexes or metal bound alkyne radical anions [31,33,34] .…”
Section: Introductionmentioning
confidence: 99%
“…[12] Given these comparably long C À N imide bonds found for complexes [2] À and [3] À we were curious if this was connected to the unique anionic character of these imido complexes, [46] as nearly all comparable 3dmetal imido complexes are either neutral or cationic. Thus, the overall neutral cobalt(I) complex K[1] [55] was reacted with Dipp-N 3 and Tripp-N 3 which gave the respective complexes K [2] and K [3]. X-Ray analysis revealed (Figure 2) an intriguing direct potassium interaction, as cation coordination to imide metal units (such as Sc 3+ ) is suggested as an important factor in modulating their properties, although direct structural evidence is lacking.…”
mentioning
confidence: 99%
“…Together with a low-spin trisphosphinoborate imido iron(II) complex by Brown et al [46] this is a unique feature compared to all other structurally characterized transition metal imido complexes which are either neutral or cationic. As such we reacted the overall neutral cobalt(I) complex [K(CoL2)] [47] with Dipp-N3 and Tripp-N3 which gave the respective imido complexes K [4] and K [5], whose structures were confirmed via X-Ray analysis (Figure 5). In solid state the potassium cation interacts with the aromatic system of the imido ligand, whose coordination sphere is completed either by two diethyl ether molecules (K [4]), or by interaction with the aryl ring of the -N(Dipp)SiMe3 ligand of a neighbouring complex (K [5]) under formation of a polymeric chain.…”
Section: Resultsmentioning
confidence: 97%